Asthma management in pediatric age group - Alzain, Mohammid; Mulla, Hatem; Junainah, Elaf; Alasmari, Abdullah; Albangali, Njood; Alqaedi, Raneem; Al-yami, Hamad; Alhawas, Fahad; Allogmani, Amjad; Alfaifi, Malak (International Journal Of Community Medicine And Public Health, 2018)
Asthma is one of the most prevalent chronic illnesses that affect the pediatric population, defined as chronic airway inflammation, remodeling of the airway wall, and airway hyper-responsiveness to leading to spasms in response to stimuli inducing a reversible airflow obstruction. The death rate from asthma around the world is as high as 0.7 per 100,000 children, therefore making it important to understand all aspect of its pathophysiology and management. We conducted this review using a comprehensive search of Pubmed, MEDLINE, and EMBASE from March 1980, through November 2017. The following search terms were used: asthma pathophysiology, chemokines, leukotriene, asthma management, steroids, beta agonist, leukotriene modifiers. Our aim was to understand detailed pathophysiology of pediatric asthma, and also have a look at the management of asthma. Optimal management of pediatric asthma is based upon a variety of measures, such as good symptomatic control, drug therapy, inhalers, but more importantly what matters is a good relationship of the physician with the patient and their care takers in order to achieve better result in short and long term. The impact of the relationship must be studied in more details to make asthma management more efficient for the pediatric group of patients.